Effect of Ambient Temperature on the Performance of a Diesel Engine Operating with Biofuel - Akasyah, M Khathri; R., Mamat; Abdul Adam, Abdullah; Amir, Aziz; Mohd Hafizil, Mat Yasin (2014)
Biofuel is an alternative fuel source for diesel engines. This resource is said to have the potential to make diesel engines more efficient and economical. The aim of this paper is to study the effect of ambient temperature on combustion and performance of a diesel engine when using biofuel. The one-dimensional numerical analysis uses the GTPower software program to simulate a commercial 4-cylinder diesel engine. The diesel engine is simulated in order to study the characteristics of engine performance when the engine is operating with ethanol and methanol as alternative fuels. The simulations were conducted at full-load condition for the engine operating with diesel, ethanol, and methanol. Ambient temperatures used for each test were 30, 40, and 50 degrees Celsius. The simulation results show that the in-cylinder pressure for ethanol is higher than for methanol and for diesel at different ambient temperatures. In other tests, methanol was found to yield a higher rate of heat release compared to ethanol and diesel fuel. It can be concluded that biofuels are excellent fuel alternatives to replace diesel fuel in the future.